Transforming Human Resource Functions with Automation - Pathak, Anchal (IGI Global, 2020)
Technology is used in various forms within today's modern market. Businesses and companies, specifically, are beginning to manage their effectiveness and performance using intelligent systems and other modes of digitization. The rise of artificial intelligence and automation has caused organizations to re-examine how they utilize their personnel and how to train employees for new skillsets using these technologies. These responsibilities fall on the shoulders of human resources, creating a need for further understanding of autonomous systems and their capabilities within organizational progres.